Psychometric testing of immigrants and natives in an acute psychiatry facility - John E. Berg (Mental Illness)
The diagnostic process after referral to an acute psychiatric treatment facility consists of more than the clinical investigation and laboratory tests. Psychometric tests in a broad range of languages may be such an augmentation of our diagnostic armamentarium. Whether such tests are in use, and how they are distributed among different patient categories was the aim of the study. All referrals in one calendar year (N=1168), as they are depicted in the hospital computerized medical records, were investigated. Fifty-six (6.1%) out of 926 ethnic Norwegians and six (3.0%) out of 198 non-Western immigrants were tested, whereas none of the 44 Western immigrants. The difference between ethnic Norwegians and the immigrants was significant (Z=-3.05 and P=0.002). Psychometric tests were thus almost not in use, and even lesser so in immigrants. Mean number of resident days was higher among those tested, 11.7 (SD=11.2) versus those not tested, 7.4 (SD=10.4) days, t=2.97 and P=0.004. Length of stay for ethnic Norwegians did not differ from that for non-Western immigrants 11.4 versus 11.7, respectively. The patients tested were older than those not tested. Mean age was 43.0 (SD=14.4) versus 38.8 (SD=12.1), with a t=2.65 and P=0.03. The difference in resident days between all immigrants and ethnic Norwegians was significant with a Z=- 2.232 and P=0.026. Level of testing was higher in ethnic Norwegians, and the tested patients stayed longer, maybe indicating more room for testing. Whether this low test-activity influences treatment quality is an unsettled question.